Analysis of Citronella Oil Additive Mixing on Engine Performance on 4-Stroke Motorcycles - M Nasir; Lasyatta Syaifullah; Rifdarmon Rifdarmon; Nuzul Hidayat (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
This study aims to determine the effect of mixing citronella oil additives as a mixture of fuel oil on motorcycle engine performance. This study uses an experimental method conducted at Teqleck Speedshop Padang using a Honda Beat Street motorcycle. Based on the results of the research that has been done, it was found that the composition of the mixture of citronella oil additives by 2% in 1 liter of Pertalite fuel oil as an ideal mixture can improve engine performance optimally with the power generated by 5.72 kW, the torque generated by 8.92 Nm, the resulting top speed is 9.1 m/s. The acceleration is 5.86 m/s2 to reach maximum speed in a short time. Penelitian ini bertujuan untuk mengetahui pengaruh pencampuran zat aditif minyak serai wangi sebagai campuran bahan bakar minyak terhadap performa mesin sepeda motor. Penelitian ini menggunakan metode ekperimen yang dilakukan di Teqleck Speedshop Padang dengan menggunakan sepeda motor Honda Beat Street. Berdasarkan hasil penelitian yang telah dilakukan didapatkan hasil bahwa dengan komposisi campuran zat aditif minyak serai wangi sebesar 2% dalam 1 liter bahan bakar minyak perlalite sebagai campuran idealnya dapat meningkatkan performa mesin secara optimal dengan daya yang dihasilkan sebesar 5,72 kW, torsi yang dihasilkan sebesar 8,92 Nm, top speed yang dihasilkan 9,1 m/s, dan akslerasi nya 5,86 m/s2 untuk mencapai kecepatan maksimum dalam waktu yang singkat.